STUDI LITERATUR - SCAFFOLDING DENGAN METODE DEFRAGMENTING STRUKTUR BERPIKIR MASALAH HOTS - Wulandari, Suci; Hayati, Rahmatul; Hendriani, Maifit (Dharmas Education Journal (DE_Journal), 2024)
Many studies have discussed the HOTS problem. Theories such as Vygotsky's scaffolding concept, where someone will be able to achieve understanding with guidance from someone who understands better, as well as the concept of defragmenting, where by breaking down the structure of thinking from understanding the problem to solving the problem, someone can have their thinking ability facilitated, especially the ability to high level thinking or HOTS. Therefore, it is necessary to analyze these concepts to study scaffolding with the defragmenting method in HOTS problems. This research uses a literature study method to examine how the scaffolding approach with the method of defragmenting thinking structures can support students in understanding HOTS in mathematics. The main focus of this research is to examine: (1) The role of scaffolding in solving HOTS mathematics problems; (2) Scaffolding concept using the method of defragmenting thinking structures; and (3) Learning characteristics that apply this method. The main finding of this literature study states that mathematics anxiety is the main obstacle in students' understanding of HOTS. However, with a scaffolding and defragmenting approach, students can break down problems into smaller parts, facilitate understanding, and improve skills in HOTS. Thus, it can be concluded that the scaffolding approach using the defragmenting method has great potential to improve students' understanding of complex mathematical problems. The implications for this literature study lead to developing a learning program that uses scaffolding with the defragmenting method to facilitate HOTS.